Delabeling penicillin and other antibiotic allergies in solid organ transplantation patients. Issue 5 (18th October 2022) - Ham, Young Yoon; Joshi, Shyam; Sukerman, Ellie
Abstract: Background: Immunocompromised populations including solid organ transplant (SOT) recipients have a high likelihood of need for antibiotic therapy for treatment of infection as well as for prophylaxis. Antibiotic allergy is commonly reported and often leads to the use of alternative, second‐line antibiotics, which have been associated with poor outcomes, increased adverse effects, and higher cost. Formal allergy assessment and allergy testing can serve as an important antimicrobial stewardship tool in optimizing antibiotic regimens for this patient population. Methods: A PubMed search with relevant keywords was performed. Review of relevant professional society guidelines was also performed. Results: Documented penicillin and sulfonamide allergies are common impediments to the treatment and prophylaxis of immunocompromised populations, but are rarely formally evaluated in practice; however, there is evidence that most patients with documented allergy to these antibiotics can, in fact, tolerate penicillins and sulfonamide antibiotics. Implementation of an antibiotic allergy evaluation and testing program has been shown to increase the use of first‐line antibiotics and can be cost saving. Conclusion: Antibiotic allergies have significant clinical consequences, especially in immunocompromised populations. Evaluation of these allergies to prevent the avoidance of first‐line antibiotics should be a standard part of the workflow for these patients, prior to transplant. Programs can be tailored to the available personnel and resources of the organization. Abstract : Graphical abstract: